ETHICS OF POOR PEOPLE IN CHRISTIAN REALISM - Vitalii Brynov ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article observes the historical background of relations between the poor and the rich. The influence of the capitalist social order on increasing inequality between rich and poor is described. It is noted that the proletarians think about social relations from the position of class conflict. It is described that the idealistic path to equality is the Marxist idea of worldwide revolution and the annihilation of class structure. It is emphasized that the destructive nature of Marxist idealism aims to the destruction of society. It is demonstrated that the ideas of the proletarians are based on envy and desire for revenge, not on moral values.